PENGARUH GAYA KEPEMIMPINAN, KOMPENSASI TERHADAP KINERJA DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) KABUPATEN KEDIRI - Atmojo, Almatri Ananda (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The usefulness of this study was used to obtain the influence of leadership style and rewards on employee performance by using work motivation as an intervening variable in PDAM Kediri Regency. For this research, a quantitative approach is used and the type of research is causal. The population in this study amounted to 98 employees. A sample of 40 respondents using the Simple Random Sampling technique. Methods of collecting data using a questionnaire, analyzed using path analysis, and tested using the SPSS 23 program. The results for the test ensure that the existence of leadership styles and compensation have a substantial relationship to employee work motivation. Work motivation substantially affects employee performance. Leadership style and compensation have a substantial effect on employee performance through work motivation as an intervening variable.